Continuing issues in U.S. national security policy - Caraley, Demetrios; Mantas, Marylena (New York : The Academy of Political Science, 2016)
"Explores the intersection between American foreign policy and presidential elections. Addresses persistent challenges and ongoing threats to U.S. national security"--
Includes bibliographical references.
Keywords: Presidents -- United States -- Election; National security -- United States; United States -- Foreign relations; United States -- Politics and government